The texts and versions of the Book of Ben Sira : transmission and interpretation - Joosten, Jan.; Rey, Jean-Sébastien. (Supplements to the Journal for the Study of Judaism, 2011)
The Book of Ben Sira comes to us in a bewildering variety of ancient textual forms. Each version shows how the book was received and interpreted in a new situation and by another community of readers. The present volume contains studies by some of the best specialists in this field of research. Each of the ancient text forms of Ben Sira-Hebrew, Greek, Syriac, and Latin-is studied in its proper context and analysed in regard to what explains the typical changes it contains.